2000
DOI: 10.1038/sj.ijir.3900513
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic pathways and adrenergic innervation of the penis

Abstract: The sympathetic nervous system is important for penile function: it mediates detumescence and may contribute to the maintenance of the penis in a non-erect state. The sympathetic preganglionic neurons are found in the intermediolateral gray matter of the spinal cord. Postganglionic neurons are located to the sympathetic chain ganglia, the inferior mesenteric, hypogastric and pelvic ganglia, and possibly to ganglia near the target organ. Sympathetic ®bres can be found in the pelvic, cavernous, and pudendal nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 32 publications
0
42
0
6
Order By: Relevance
“…Noradrenaline is excitatory in nature and causes contraction of smooth muscular cells (Owman and Stjernquist, 1988;Keast, 1999;Andersson, 2000;Andersson et al, 2000). As noradrenergic fibers are usually found in the muscular coat or around blood vessels of genital organs (Kaleczyc et al, 1993;Majewski et al, 1995;Czaja et al, 1996;Anderson and Stief, 1997), we think that the TH-or DbH-IR RDL neurons exert contemporaneously their influence on the smooth muscular cells and on the blood vessels of the smooth RPM and of the striated BSM.…”
Section: Th-or Dbh-immunoreactivitymentioning
confidence: 99%
“…Noradrenaline is excitatory in nature and causes contraction of smooth muscular cells (Owman and Stjernquist, 1988;Keast, 1999;Andersson, 2000;Andersson et al, 2000). As noradrenergic fibers are usually found in the muscular coat or around blood vessels of genital organs (Kaleczyc et al, 1993;Majewski et al, 1995;Czaja et al, 1996;Anderson and Stief, 1997), we think that the TH-or DbH-IR RDL neurons exert contemporaneously their influence on the smooth muscular cells and on the blood vessels of the smooth RPM and of the striated BSM.…”
Section: Th-or Dbh-immunoreactivitymentioning
confidence: 99%
“…It has been suggested that this supraspinal vasodilator pathway is a sympathetic cholinergic pathway, operating through cholinergic (NANC) neurons in the pelvic plexus. 23 Sympathetic fibres are found to take synapses in the pelvic plexus with NANC fibres, suggesting another mechanism for how patients with sacral lesions may have hypothetically psychogenic erections. Notwithstanding the fact that the sympathetic nervous system is considered to be the antierectile centre, this pathway may also facilitate erections after an injury to parasympathetic pathways.…”
Section: Neuroanatomy Related To Sexual Dysfunction K Everaert Et Almentioning
confidence: 99%
“…The CC contracts in response to the activation of adrenergic a-receptors 18,19 and relaxes when adrenergic b-receptors are activated. 20,21 That is, activation of a-adrenoreceptors is involved in the flaccid state of the CC and suppression of penile erection. 22 In contrast, activating b-adrenoreceptors is involved in an erection.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In contrast, mixed b 1 -and b 2 -adrenoceptors mediate relaxation reactions in the horse CC. 21 Furthermore, atypical b-adrenoceptors and b 2 -adrenoceptors mediate the primary relaxation reaction in rabbits. 25 However, in our study, the b-adrenoceptor subtype of the CC that higenamine mediated the major relaxation reaction could not be assessed using the non-selective adrenergic b-antagonist propranolol.…”
Section: Discussionmentioning
confidence: 99%